2021
DOI: 10.3389/fevo.2021.683722
|View full text |Cite
|
Sign up to set email alerts
|

Endemism Patterns of Planthoppers (Fulgoroidea) in China

Abstract: Studies on endemism are always of high interest in biogeography and contribute to better understanding of the evolution of species and making conservation plans. The present study aimed to investigate the endemism patterns of planthoppers in China by delimiting centers of endemism and areas of endemism. We collected 6,907 spatial distribution records for 860 endemic planthopper species from various resources. Centers of endemism were identified using weighted endemism values at 1° grid size. Parsimony analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 68 publications
(89 reference statements)
0
20
0
Order By: Relevance
“…In recent years, a number of biogeographic and evolutionary studies have implemented and applied the areas of endemism (AOEs) to resolve practical issues (Nelson and Platnick, 1981;Anderson, 1994;Huang et al, 2006Huang et al, , 2008Huang et al, , 2010López-Pujol et al, 2011;Yuan et al, 2014;Gao et al, 2018;Noroozi et al, 2018;Zhao et al, 2021). The definition of AOEs is generally agreed as a distribution congruence of at least two restricted species (Cracraft, 1985;Harold and Mooi, 1994;Morrone, 1994;Linder, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent years, a number of biogeographic and evolutionary studies have implemented and applied the areas of endemism (AOEs) to resolve practical issues (Nelson and Platnick, 1981;Anderson, 1994;Huang et al, 2006Huang et al, , 2008Huang et al, , 2010López-Pujol et al, 2011;Yuan et al, 2014;Gao et al, 2018;Noroozi et al, 2018;Zhao et al, 2021). The definition of AOEs is generally agreed as a distribution congruence of at least two restricted species (Cracraft, 1985;Harold and Mooi, 1994;Morrone, 1994;Linder, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These areas are supposed to be characterized by a stable climate, and they therefore offered considerable opportunities for past speciation and persistence (Jetz et al, 2004). This long-term evolution may explain why AOEs often contain high species richness, which is less predictable by contemporary environment alone (Jetz et al, 2004;López-Pujol et al, 2011;Fjeldså et al, 2012), so dozens of biogeographers and evolutionary biologists have shown their interests in evaluating the causes for the presence of AOEs (Nelson and Platnick, 1981;Anderson, 1994;Huang et al, 2006Huang et al, , 2008Huang et al, , 2010López-Pujol et al, 2011;Yuan et al, 2014;Gao et al, 2018;Noroozi et al, 2018;Zhao et al, 2021). The montane system, which accounts for a large portion of biodiversity hotspots and harbors many narrow-ranged species (Orme et al, 2005;Fjeldså et al, 2012;Wu et al, 2017), has been anticipated as refugia with stable climates and heterogeneous topography, and hence facilitates the persistence and speciation (Favre et al, 2015;Zhao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations